Culturally Relevant Education: Extending the Conversation to Religious Diversity. (2nd July 2016) - Aronson, Brittany; Amatullah, Tasneem; Laughter, Judson
Abstract : Culturally relevant education represents a wide collection of pedagogies of opposition to social injustice and holds a commitment to collective empowerment and social justice. By using culturally relevant education as a framework, we make the case to include religious diversity as a part of culturally relevant education intentionally. We believe that by opening the dialogue to include religious diversity, we are working together as educators to promote social justice in schools that benefits all children regardless of their religious backgrounds. We synthesize successful examples of culturally relevant education in connection to religion. Further, we argue for teacher educators to incorporate discussion of religious diversity as part of multicultural and social justice teacher education.